Introduction to derivative securities, financial markets, and risk management - Jarrow, Robert; Chatterjea, Arkadev (London World Scientific, 2019)
Written by Robert Jarrow, one of the true titans of finance and his former student Arkadev Chatterjee, Introduction to Derivatives is the first text developed from the ground up for students taking the introductory derivatives course. The math is presented at the right level and is always motivated by what s happening in the financial markets. And, as one of the developers of the Heath-Jarrow-Morton Model, Robert Jarrow presents a novel, accessible way to understand this important topic.".
Keywords: Derivative securities; Financial institutions; Capital market